Specificity of DNA import into isolated mitochondria from plants and mammals - Koulintchenko, M.V.; Ibrahim, N.; Klimenko, E.S.; Konstantinov, Yu.M.; Weber-Lotfi, F.; Dietrich, A. (Вiopolymers and Cell, 2014)
Aim. Investigation of different features of DNA import into plant and human mitochondria, for a better understanding of mitochondrial genetics and generation of biotechnological tools. Methods. DNA up-take experiments with isolated plant mitochondria, using as substrates various sequences associated or not with the specific terminal inverted repeats (TIRs) present at each end of the plant mitochondrial linear plasmids. Results. It was established that the DNA import efficiency has a non-linear dependence on DNA size. It was shown that import into plant mitochondria of DNA molecules of «medium» sizes, i. e. between 4 and 7 kb, barely has any sequence specificity: neither TIRs from the 11.6 kb Brassica plasmid, nor TIRs from the Zea mays S-plasmids influenced DNA import into Solanum tuberosum mitochondria. Conclusions. The data obtained support the hypothesis about species-specific import mechanism operating under the mitochondrial linear plasmids transfer into plant mitochondria.